Low-level laser therapy in the treatment of recurrent aphthous stomatitis and oral lichen planus: a literature review - Ślebioda, Zuzanna; Dorocka-Bobkowska, Barbara (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Recurrent aphthous stomatitis (RAS) and oral lichen planus (OLP) present inflammatory, recurrent diseases of the oral mucosa with not fully understood aetiology. Despite numerous attempts to discover an effective treatment for RAS and OLP, the current main treatment strategies are largely confined to the reduction of symptoms. Low-level laser therapy (LLLT) is of interest as a novel treatment modality. The aim of the paper was to discuss the mechanism of action and the biological effects of LLLT and to critically review and summarize recent clinical reports on the management of RAS and OLP. Most of the studies demonstrated the beneficial effect of LLLT in accelerating the healing process and pain reduction. However, the results should be interpreted with caution due to the limited number of studies available and empirical design using various irradiation parameters.